STUDI TEGANGAN-REGANGAN SALOK ( Tinjauan Terhadap Konstruksi Ramp Stadion Maguwoharjo, Sleman ) - Pramudiyanto, Pramudiyanto (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
Abstract This research aims to gather information of computer application of structural mechanics to determine the distribution of stress and strain of the cross section. The research focuses on the actors of computer users, the data analyzing, and stress-strain behavior. This research applies experimental approach. The chosen subject is the ramp construction of The Maguwoharjo Soccer Stadium, Sleman. The construction is being chosen with the reason of a uniqueconstruction. The ramp then being analyzed mathematically using VisualFEA to determined the stress-strain behavior. The research result show that the use of specific computer programs, and for the specific case given, the distribution of stress and strain still linear. The analysis show that the distribution of stress still follow the linearity, even the analysis method using the different way. Keywords: computer user, structural mechanics, stress-strain.